Energetic profiles of the Yo-Yo intermittent recovery tests 1 and 2 - Kaufmann, S.; Hoos, O.; Kuehl, T.; Tietz, T.; Reim, D.; Fehske, K.; Latzel, R.; Beneke, R. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To analyze the energetic profiles of the Yo-Yo Intermittent Recovery Tests 1 and 2 (YYIR1 and YYIR2). Methods: Intermittent running distance (IR1D and IR2D), time to exhaustion (IR1T and IR2T), and total recovery time between shuttles (IR1R and IR2R) were measured in 10 well-trained male athletes (age 24.4 [2.0] y, height 182 [1] cm, weight 75.8 [7.9] kg). Respiratory gases and blood lactate (BLC) were obtained preexercise, during exercise, and until 15 min postexercise. Metabolic energy, average metabolic power , and energy share (percentage of aerobic [WAER], anaerobic lactic [WBLC], and anaerobic alactic energy system [WPCr]) were calculated using the PCr-La-O2 method. Results: Peak oxygen consumption was possibly higher in YYIR2 (60.3 [5.1] mL·kg-1·min-1) than in YYIR1 (P = .116, 57.7 [4.5] mL·kg-1·min-1, d = -0.58). IR1D, IR1T, and IR1R were very likely higher than IR2D, IR2T, and IR2R, respectively (P < .001, 1876 [391] vs 672 [132] m, d = -2.83; P < .001, 916 [175] vs 304 [57] s, d = -3.03; and P < .001, 460 [100] vs 150 [40] s, d = -2.83). Metabolic energy was most likely lower in YYIR2 than in YYIR1 (P < .001, 493.5 [118.1] vs 984.8 [171.7] kJ, d = 3.24). Average metabolic power was most likely higher in YYIR2 than in YYIR1 (P < .001, 21.5 [1.7] vs 14.5 [2.2] W·kg-1, d = 3.54). When considering aerobic phosphocreatine restoration during breaks between shuttles, WAER (P = .693, 49% [10%] vs 48% [5%], d = -0.16) was similar, WPCr (P = .165, 47% [11%] vs 42% [6%], d = -0.54) possibly higher, and WBLC (P < .001, 4% [1%] vs 10% [3%], d = 1.95) almost certainly lower in YYIR1 than in YYIR2. Conclusions: WAER and WPCr are predominant in YYIR1 and YYIR2 with almost identical WAER. Higher IR1D and IR1T in YYIR1 result in higher metabolic energy but lower average metabolic power and slightly lower peak oxygen consumption. Higher IR1R allows for higher reliance on WPCr in YYIR1, while YYIR2 requires a higher fraction of WBLC.